REBROWSING ON BIRCH (BETULA PENDULA AND B. PUBESCENS) STEMS BY MOOSE - Bergström, R. (Lakehead University, 1983)
Within the Sunnäs moose (Alces alces) enclosure (6.2 km2) in central Sweden 134 stems of Betula pendula and 111 of B. pubescens were permanently tagged. Winter browsing by moose was recorded every spring in four consecutive years. The observed distribution of the number of trees in classes with different “browsing history” differed significantly from what could be expected. The difference was most striking in the two groups “unbrowsed all years” and “browsed all years”. In these groups observed frequencies were considerably larger than expected. There was also a quantitative relationship: the more a plant was browsed as a total during the first three years the more it was browsed in the fourth year. The results are discussed in relation to food selection and dynamics of the moose-browse system.